Carbamate derivatives and sesquiterpenoids from the South China Sea gorgonian Melitodes squamata - Huang, Li-Si; He, Fei; Huang, Hui; Zhang, Xiao-Yong; Qi, Shu-Hua (Beilstein Journal of Organic Chemistry, 2012)
Five carbamate derivatives, obtucarbamates C and D (1, 2), dimethyl ((carbonylbis(azanediyl))bis(2-methyl-5,1-phenylene))dicarbamate (3), obtucarbamates A and B (4, 5), and four aromadendrane-type sesquiterpenoids, (+)-4β-N-methenetauryl-10β-methoxy-1β,5α,6β,7β-aromadendrane (6), (−)-4β-N-methenetauryl-10β-methoxy-1β,5β,6α,7α-aromadendrane (7), (−)-4α,10β-aromadendranediol (8), (+)-4β,10β-aromadendranediol (9) were obtained from the South China Sea gorgonian coral Melitodes squamata Nutting. Compounds 1, 2, 6, and 7 were new, and their structures were established by spectroscopic analyses. Compounds 6 and 7 contained a taurine group that was rarely found in marine natural compounds, and 7 showed moderate antibacterial activity. The possible biosynthesis routes of 1–5 were conjectured.
Keywords: carbamate; gorgonian; Melitodes squamata; sesquiterpenoid

(untitled) - Coll, J. C. (Chem. Rev., 1992)

(untitled) - Rodríguez, A. D. (Tetrahedron, 1995)

(untitled) - Shao, C. L.; Fu, X. M.; Wang, C. Y.; Han, L.; Liu, X.; Fang, Y. C.; Li, G. Q.; Zeng, X. Q.; Liu, G. X.; Guan, H. S. (Period. Ocean Univ. China, 2009)

(untitled) - Kobayashi, M.; Kanda, F. (J. Chem. Soc., Perkin Trans. 1, 1991)

(untitled) - Brown, G. W.; Cohen, P. P. (Biochem. J., 1960)

(untitled) - Kuo, Y. H.; Jou, M. H. (Chem. Express, 1990)

(untitled) - Goldsby, G.; Burke, B. A. (Phytochemistry, 1987)

(untitled) - Bohlmann, F.; Grenz, M.; Jakupovic, J.; King, R. M.; Robinson, H. (Phytochemistry, 1983)

(untitled) - Beechan, C. M.; Djerassi, C.; Eggert, H. (Tetrahedron, 1978)

(untitled) - Jizba, J.; Laudová, V.; Samek, Z.; Ubik, K.; Novotny, L. (Collect. Czech. Chem. Commun., 1981)

(untitled) - Liu, H.-J.; Wua, C.-L.; Becker, H.; Zapp, J. (Phytochemistry, 2000)

(untitled) - De Marino, S.; Iorizzi, M.; Zollo, F.; Debitus, C.; Menou, J.-L.; Ospina, L. F.; Alcaraz, M. J.; Payá, M. (J. Nat. Prod., 2000)

(untitled) - Xynas, R.; Capon, R. J. (Aust. J. Chem., 1989)

(untitled) - Simo, S.; Oja, P. S. (Proc. West. Pharmacol. Soc., 2007)